"Personalized Excision" of Malignant Melanoma—Need for a Paradigm Shift in the Beginning Era of Personalized Medicine. (December 2019) - Weyers, Wolfgang
Abstract : Abstract: The premises on which guidelines for the excision of primary cutaneous melanoma are based are illogical and fail to take into account peculiarities of the individual lesion. The horizontal margins of excision continue to be adjusted to the vertical thickness of the neoplasm, and recommended clinical margins do not reflect the histopathologic borders of melanoma. Micrographically controlled surgery has become accepted for acral melanomas and melanomas of the face and neck but not for melanomas on the trunk, arms, and legs, although the latter tend to be more sharply confined. Extending margins of excision for the purpose of removing inapparent metastases is fallacious because the latter are rare, their localization cannot be foretold, and satellite metastases are usually associated with distant metastases, so that patients do not profit from early removal of cutaneous lesions. The only meaningful objective of excision is complete removal of the primary melanoma. The success of excision must be controlled histopathologically. Because of limitations of the method, a histopathologic safety margin should be observed that must depend on the characteristics of the individual lesion. In sharply confined melanomas, a histopathologic margin of at least 1 mm is sufficient. In the case of poor demarcation, with solitary atypical melanocytes extending far beyond the bulk of the lesion, a broader histopathologic safety margin is advisable. Special caution should be exercised in the presence of regression and for desmoplastic melanomas, acral melanomas, and melanomas on the face and scalp. Instead of wide and deep excisions with standardized margins, "personalized excisions" are required for primary cutaneous melanoma. The concept of clinical safety margins is a relic of former times that has no place in modern medicine.